130 germplasm from 9 NARS partners fingerprinted for 43 QTLs/genes in Asian and Sub-Saharan Africa - CGIAR Research Program on Rice (2021)
130 germplasm from 9 NARS partners were fingerprinted for 43 QTLs/causative genes targeted at 20 unique traits. The traits included grain quality traits, abiotic stress tolerance as well as disease resistance.